Aqueous dispersions and films of halogenated vinyl copolymers

By optimizing the composition of the aqueous dispersion of halide ethylene copolymer, combining the specific monomer ratio and melting peak-temperature ratio, the problem of insufficient water vapor barrier properties and long-term film formation properties in the prior art is solved, and efficient water vapor barriers and excellent film formation properties are achieved.

CN115244091BActive Publication Date: 2025-03-25ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202180020171.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-27
Filing Date
2021-03-10
Publication Date
2025-03-25
Estimated Expiration
2041-03-10

AI Technical Summary

Technical Problem

The existing aqueous ethylene halogenated copolymer dispersions have shortcomings in improving water vapor barrier properties and film formation properties after long-term preservation, and it is difficult to take into account both.

Method used

A specific composition of ethylene halogenated copolymer aqueous dispersion is used, which comprises structural units from ethylene halogenated monomers and comonomers with a reactivity ratio of less than 0.7 with respect to vinylidene chloride, and the composition of the aqueous dispersion is optimized by controlling the melting peak temperature ratio and monomer ratio.

Benefits of technology

The coated film maintains high water vapor barrier properties and maintains excellent film formation properties after long-term storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003840089190000101
    Figure BDA0003840089190000101
  • Figure BDA0003840089190000271
    Figure BDA0003840089190000271
  • Figure HDA0003840089200000011
    Figure HDA0003840089200000011
Patent Text Reader

Abstract

The present invention aims to provide an aqueous dispersion of a vinyl halide copolymer which can maintain high water vapor barrier properties after coating and has good film-forming properties after long-term storage. The aqueous dispersion of the vinyl halide copolymer of the present invention is characterized in that it comprises a vinyl halide copolymer, the vinyl halide copolymer comprising a structural unit derived from a vinyl halide monomer and a structural unit derived from a comonomer having a reactivity ratio r1 of less than 0.7 with respect to a total of 100 parts by mass of the structural unit derived from the vinyl halide monomer, the structural unit derived from the comonomer having a reactivity ratio r1 of less than 0.7, and the structural unit derived from the comonomer having a reactivity ratio r1 of 0.7 or more, the mass ratio of the structural unit derived from the comonomer having a reactivity ratio r1 of less than 0.7 is 1 part by mass or more, and when the area of ​​a melting peak having a melting peak temperature of 170°C or more is S1 and the area of ​​a melting peak having a melting peak temperature of less than 170°C is S2, S1 / (S1+S2) is 0 or more and 0.33 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an aqueous dispersion of a halogenated vinyl copolymer and a film having a layer coated with the aqueous dispersion. Background Art

[0002] In order to maintain the quality of food and medicine, the film used to package them needs to fully block the gases such as oxygen, nitrogen, carbon dioxide, and water vapor in the atmosphere to seal them. In this regard, among various resins, the film having a layer formed of a halogenated vinyl copolymer aqueous dispersion, especially a vinylidene chloride copolymer aqueous dispersion resin, has excellent barrier properties against water vapor and oxygen, and is therefore very suitable for food and medicine packaging purposes.

[0003] In recent years, packaging films have been required to have higher gas barrier properties for the following reasons.

[0004] 1) Maintain the quality of food materials and the efficacy of medicines for a longer period of time;

[0005] 2) Thin-film manufacturing to meet the demand for improved extrudability of the contents of packaged products as the population ages;

[0006] 3) Thin film production to improve productivity.

[0007] Patent Documents 1 to 5 are known as vinylidene chloride aqueous dispersions constituting films having barrier properties.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: International Publication No. 2013 / 125699 Pamphlet

[0011] Patent Document 2: Japanese Patent Application No. 2001-526315

[0012] Patent Document 3: Japanese Patent Application Laid-Open No. 05-202107

[0013] Patent Document 4: Japanese Patent Application Publication No. 2018-127523

[0014] Patent Document 5: Japanese Patent Application Laid-Open No. 60-192768 Summary of the invention

[0015] Problems to be solved by the invention

[0016] Regarding the ethylene halide copolymers described in Patent Documents 1 to 3, it is difficult to further improve the water vapor barrier properties in terms of monomer combination.

[0017] In contrast, as described in Patent Documents 4 and 5, copolymers obtained by copolymerizing a comonomer having a reactivity ratio r1 of less than 0.7 with respect to vinylidene chloride have high water vapor barrier properties. On the other hand, since they are easily crystallized even in the form of a water dispersion, they have a problem of deteriorating film-forming properties over time after long-term storage.

[0018] Therefore, in the aqueous dispersions described in Patent Documents 1 to 5, it is difficult to achieve both film-forming properties after long-term storage and high barrier properties of a film having a layer formed of the aqueous dispersion.

[0019] Therefore, an object of the present invention is to provide an aqueous dispersion of a vinyl halide copolymer which can maintain high water vapor barrier properties after coating and has good film-forming properties after long-term storage.

[0020] Means for solving problems

[0021] The present invention has been completed after repeated intensive studies to solve the above-mentioned problems and, as a result, has found that a film coated with an aqueous dispersion containing a halogenated vinyl copolymer of a specific composition and having a specific melting peak temperature ratio can maintain high water vapor barrier properties and has excellent film-forming properties after long-term storage.

[0022] That is, the present invention is as follows. [1]

[0024] An aqueous dispersion of a vinyl halide copolymer, characterized in that the aqueous dispersion contains a vinyl halide copolymer, the vinyl halide copolymer contains a structural unit derived from a vinyl halide monomer and a structural unit derived from a comonomer having a reactivity ratio r1 of less than 0.7 with respect to vinylidene chloride, wherein the mass ratio of the structural unit derived from the comonomer having a reactivity ratio r1 of less than 0.7 is 1 mass part or more relative to a total of 100 mass parts of the structural unit derived from the vinyl halide monomer, the structural unit derived from the comonomer having a reactivity ratio r1 of less than 0.7, and the structural unit derived from the comonomer having a reactivity ratio r1 of 0.7 or more.

[0025] When the area of ​​the melting peak having a melting peak temperature of 170° C. or higher is defined as S1 and the area of ​​the melting peak having a melting peak temperature of less than 170° C. is defined as S2, S1 / (S1+S2) is 0 or more and 0.33 or less. [2]

[0027] The aqueous dispersion of the vinyl halide copolymer as described in [1], wherein the vinyl halide monomer is vinylidene chloride. [3]

[0029] The aqueous dispersion of the vinyl halide copolymer as described in [1] or [2], wherein the comonomer having the reactivity ratio r1 of less than 0.7 is at least one selected from the group consisting of a monomer having a nitrile group, a monomer having a carboxyl group, and methyl methacrylate. [4]

[0031] The aqueous dispersion of a vinyl halide copolymer as described in any one of [1] to [3], wherein

[0032] The comonomer having the reactivity ratio r1 of less than 0.7 includes a monomer having a nitrile group,

[0033] The mass proportion of the structural unit derived from the monomer having a nitrile group is greater than 1.5 parts by mass relative to a total of 100 parts by mass of the structural unit derived from the above-mentioned halogenated vinyl monomer, the structural unit derived from the above-mentioned comonomer having the above-mentioned reactivity ratio r1 of less than 0.7, and the structural unit derived from the above-mentioned comonomer having the above-mentioned reactivity ratio r1 of 0.7 or more. [5]

[0035] The aqueous dispersion of the vinyl halide copolymer as described in [3] or [4], wherein the comonomer having the reactivity ratio r1 of less than 0.7 contains methacrylonitrile. [6]

[0037] An aqueous dispersion of a vinyl halide copolymer as described in [5], wherein the mass ratio of the structural unit derived from methacrylonitrile is 5 parts by mass or more relative to a total of 100 parts by mass of the structural unit derived from the vinyl halide monomer, the structural unit derived from the comonomer having the reactivity ratio r1 of less than 0.7, and the structural unit derived from the comonomer having the reactivity ratio r1 of 0.7 or more. [7]

[0039] The aqueous dispersion of a vinyl halide copolymer as described in any one of [3] to [6], wherein the monomer having a nitrile group is methacrylonitrile. [8]

[0041] The aqueous dispersion of the halogenated vinyl copolymer according to any one of [3] to [7], wherein the monomer having a carboxyl group is acrylic acid, itaconic acid, maleic acid or methacrylic acid. [9]

[0043] The aqueous dispersion of the vinyl halide copolymer according to any one of [1] to [8], wherein the mass ratio of the structural unit derived from the comonomer having a reactivity ratio r1 of less than 0.7 is 5 parts by mass or more and 20 parts by mass or less.

[10]

[0045] The aqueous dispersion of the vinyl halide copolymer according to any one of [1] to [8], wherein the mass ratio of the structural units derived from the vinyl halide monomer is 86 parts by mass or more relative to 100 parts by mass of the total of the structural units derived from the vinyl halide monomer, the structural units derived from the comonomer having a reactivity ratio r1 of less than 0.7, and the structural units derived from the comonomer having a reactivity ratio r1 of 0.7 or more.

[0046] The mass ratio of the structural unit derived from the comonomer having a reactivity ratio r1 of less than 0.7 is 14 parts by mass or less.

[11]

[0048] The aqueous dispersion of the ethylene halide copolymer according to any one of [1] to

[10] , comprising 20 parts by mass or less of a crystal nucleating agent based on 100 parts by mass of the ethylene halide copolymer.

[12]

[0050] A film characterized by having a layer coated with the aqueous dispersion of the halogenated vinyl copolymer described in any one of [1] to

[11] .

[0051] Effects of the Invention

[0052] The aqueous dispersion of the vinyl halide copolymer of the present invention has the following effects: the film after coating can maintain high water vapor barrier properties and has excellent film-forming properties after long-term storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is a diagram showing an example of a melting peak.

[0054] Figure 2 This is a diagram for explaining the method of drawing the baseline of a peak (I).

[0055] Figure 3 This is a diagram for explaining the method of drawing the peak baseline (II).

[0056] Figure 4 This is a diagram for explaining the method of drawing the peak baseline (II).

[0057] Figure 5 This is a diagram for explaining the method for drawing the peak baseline (III).

[0058] Figure 6 This is a diagram for explaining the method of drawing the peak baseline (IV).

[0059] Figure 7 This is an example of determining the peak area from an endothermic curve. DETAILED DESCRIPTION

[0060] The specific implementation mode of the present invention (hereinafter referred to as "this implementation mode") is described in detail below. The following implementation mode is an example for explaining the present invention and is not intended to limit the present invention to the following content. The present invention can be implemented by appropriately deforming within the scope of its main points.

[0061] [Aqueous dispersion]

[0062] The aqueous dispersion of the present embodiment contains a halogenated vinyl copolymer.

[0063] (Ethylene Halogen Copolymer)

[0064] The vinyl halide copolymer contains at least a structural unit derived from a vinyl halide monomer and a structural unit derived from a comonomer having a reactivity ratio r1 with respect to vinylidene chloride of less than 0.7. The vinyl halide copolymer may also contain a structural unit derived from other monomers.

[0065] It should be noted that in this specification, a monomer copolymerizable with the above-mentioned vinyl halide monomer is sometimes referred to as a "comonomer". Examples of the above-mentioned comonomer include a comonomer having a reactivity ratio r1 of less than 0.7 with respect to vinylidene chloride (sometimes referred to as a "comonomer having a reactivity ratio r1 of less than 0.7"), a comonomer having a reactivity ratio r1 of 0.7 or more with respect to vinylidene chloride (sometimes referred to as a "comonomer having a reactivity ratio r1 of 0.7 or more"), and the like.

[0066] In addition, the above-mentioned other monomers refer to monomers that do not belong to the above-mentioned vinyl halide monomers and the above-mentioned comonomers.

[0067] The mass ratio of the structural unit derived from the vinyl halide monomer is preferably 80 parts by mass or more, more preferably 85 parts by mass or more, further preferably 86 parts by mass or more, and particularly preferably 87 parts by mass or more, relative to 100 parts by mass of the total of the structural unit derived from the vinyl halide monomer, the structural unit derived from the comonomer having a reactivity ratio r1 of less than 0.7, and the structural unit derived from the comonomer having a reactivity ratio r1 of 0.7 or more. In addition, the mass ratio is preferably 99 parts by mass or less, more preferably 95 parts by mass or less, further preferably 93 parts by mass or less, further preferably 92 parts by mass or less, and particularly preferably 90 parts by mass or less.

[0068] It should be noted that the mass ratio of the structural units derived from the above-mentioned vinyl halide monomer, the mass ratio of the structural units derived from the above-mentioned comonomer having a reactivity ratio r1 of less than 0.7 described later, and the mass ratio of the structural units derived from the comonomer having a reactivity ratio r1 of 0.7 or more described later can be used in a manner such that the total of the structural units derived from the above-mentioned vinyl halide monomer, the structural units derived from the above-mentioned comonomer having a reactivity ratio r1 of less than 0.7, and the structural units derived from the above-mentioned comonomer having a reactivity ratio r1 of 0.7 or more is 100 parts by mass.

[0069] The mass ratio of the structural unit derived from the comonomer having a reactivity ratio r1 of less than 0.7 is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, further preferably 14 parts by mass or less, and particularly preferably 13 parts by mass or less, relative to 100 parts by mass of the total of the structural unit derived from the vinyl halide monomer, the structural unit derived from the comonomer having a reactivity ratio r1 of less than 0.7, and the structural unit derived from the comonomer having a reactivity ratio r1 of 0.7 or more. In addition, the above mass ratio is 1 part by mass or more, preferably 5 parts by mass or more, and particularly preferably 7 parts by mass or more.

[0070] In 100% by mass of the above-mentioned vinyl halide copolymer, the ratio of the total mass of the structural units derived from the above-mentioned vinyl halide monomer and the structural units derived from the above-mentioned comonomer having a reactivity ratio r1 of less than 0.7 is preferably 85% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and particularly preferably 100% by mass.

[0071] The vinyl halide copolymer may optionally contain a structural unit derived from a comonomer having a reactivity ratio r1 of 0.7 or more with respect to vinylidene chloride.

[0072] The mass proportion of the structural units derived from the above-mentioned comonomer having a reactivity ratio r1 of 0.7 or more is preferably 5 parts by mass or less, and more preferably 3 parts by mass or less, relative to 100 parts by mass of the total of the structural units derived from the above-mentioned vinyl halide monomer, the structural units derived from the above-mentioned comonomer having a reactivity ratio r1 of less than 0.7, and the structural units derived from the above-mentioned comonomer having a reactivity ratio r1 of 0.7 or more.

[0073] When the mass ratio of the above components in the above ethylene halide copolymer is within the above range, the film having a layer formed of the aqueous dispersion of the ethylene halide copolymer of the present embodiment can exhibit barrier properties sufficient to maintain the quality of the content.

[0074] The above-mentioned vinyl halide monomer is preferably vinylidene chloride.

[0075] The above-mentioned vinyl halide monomers may be used alone or in combination of two or more.

[0076] Regarding the reactivity ratio r1 relative to vinylidene chloride, when vinylidene chloride is used as monomer 1 (M1) and the comonomer is used as monomer 2 (M2), the reaction rate constant of the reaction between the free radical of M1 and M1 is k11, and the reaction rate constant of the reaction between the free radical of M1 and M2 is k12. The normal monomer reactivity ratio calculated by r1 = k11 / k12 is the reactivity ratio r1 relative to vinylidene chloride. As the above reactivity ratio r1, the value described in Polymer Handbook Forth Edition (ISBN: 0-471-48171-8) can be used. In the case where multiple values ​​are described, the lowest value is used.

[0077] If there is no record in the Polymer Handbook Forth Edition, the value of the known literature is used. If there is no value in the known literature, bulk polymerization, solution polymerization, or suspension polymerization can be performed to determine the reactivity ratio by the Kelen-Tudos method. If the reactivity ratio r1 varies due to multiple measurements, the lowest value among them is used.

[0078] Among the monomers constituting the synthesized halogenated vinyl copolymer, when the proportion of monomers with unknown reactivity ratio r1 is relatively small and the value of the reactivity ratio r1 of the monomers with unknown reactivity ratio r1 does not change in magnitude relative to the threshold to be compared, it can be directly treated as unknown. For example, the mass composition of VDC / MA / "monomers with unknown reactivity ratio r1" is 90 / 8 / 2. If it is to be determined whether the proportion of monomers with reactivity ratio r1 less than 0.7 is less than 4 parts by mass, even if the reactivity ratio r1 of the monomers with unknown reactivity ratio r1 is less than 0.7, the proportion of monomers with reactivity ratio r1 less than 0.7 is only 2 parts by mass as a whole. In this case, the reactivity ratio r1 of the monomers with unknown reactivity ratio r1 can be directly treated as unknown.

[0079] As an example, the reactivity ratios r1 of several monomers with respect to vinylidene chloride are shown.

[0080] Butyl acrylate: 0.84

[0081] Ethyl acrylate: 0.58

[0082] Methyl acrylate: 0.7

[0083] Acrylic acid: 0.29

[0084] Acrylonitrile: 0.28

[0085] Methyl methacrylate: 0.02

[0086] Methacrylic acid: 0.15

[0087] Methacrylonitrile: 0.036

[0088] Vinyl chloride: 1.8

[0089] As the comonomer having a reactivity ratio r1 of less than 0.7 with respect to vinylidene chloride, a known monomer can be used, and preferably methyl methacrylate (hereinafter referred to as MMA), a monomer having a nitrile group, and a monomer having a carboxyl group.

[0090] The reactivity ratio r1 of the comonomer having a reactivity ratio r1 of less than 0.7 with respect to vinylidene chloride may be greater than 0.

[0091] The comonomer having a reactivity ratio r1 of less than 0.7 may be used alone or in combination of two or more.

[0092] The monomer having a nitrile group is preferably acrylonitrile (hereinafter referred to as AN) or methacrylonitrile (hereinafter referred to as MAN), and particularly preferably methacrylonitrile.

[0093] The monomer having a carboxyl group is preferably acrylic acid (hereinafter referred to as AA), itaconic acid, maleic acid, or methacrylic acid (hereinafter referred to as MAA), and more preferably acrylic acid or methacrylic acid.

[0094] As the monomer having a reactivity ratio r1 of 0.7 or more with respect to vinylidene chloride, a known monomer can be used, and vinyl chloride, methyl acrylate (hereinafter referred to as MA), and butyl acrylate are preferred.

[0095] The comonomer having a reactivity ratio r1 of less than 0.7 preferably contains at least a monomer having a nitrile group, more preferably contains at least methacrylonitrile. It is preferred that the monomer having a nitrile group contained in the comonomer having a reactivity ratio r1 of less than 0.7 is only methacrylonitrile.

[0096] Relative to the total of 100 parts by mass of the structural units derived from the above-mentioned vinyl halide monomer, the structural units derived from the comonomer having a reactivity ratio r1 of less than 0.7, and the structural units derived from the comonomer having a reactivity ratio r1 of 0.7 or more, the mass ratio of the structural units derived from the above-mentioned monomer having a nitrile group is preferably 1 part by mass or more, more preferably greater than 1.5 parts by mass, further preferably 3 parts by mass or more, and preferably 30 parts by mass or less, more preferably 20 parts by mass or less. Here, in the case where the monomer having a nitrile group includes two or more, the above-mentioned mass ratio of the structural units derived from the monomer having a nitrile group refers to the total mass ratio of the structural units derived from all monomers having a nitrile group.

[0097] The mass ratio of the structural unit derived from methacrylonitrile is preferably greater than 0 mass parts, more preferably 1 mass part or more, further preferably greater than 1.5 mass parts, further preferably 3 mass parts or more, particularly preferably 5 mass parts or more, and preferably 30 mass parts or less, more preferably 20 mass parts or less, relative to 100 mass parts of the total of the structural units derived from the above-mentioned vinyl halide monomer, the structural units derived from the comonomer having a reactivity ratio r1 of less than 0.7, and the structural units derived from the comonomer having a reactivity ratio r1 of 0.7 or more. Here, in the case where methacrylonitrile and other monomers having a nitrile group are included as the monomer having a nitrile group, the above-mentioned mass ratio of the structural unit derived from methacrylonitrile refers to the mass ratio of the structural unit derived from methacrylonitrile alone excluding other monomers having a nitrile group.

[0098] By copolymerizing these monomers, a film produced from the aqueous dispersion of the above-mentioned vinyl halide copolymer has high water vapor barrier properties.

[0099] The monomer composition of the vinyl halide copolymer can be evaluated by dissolving a sample collected by the following method in tetrahydrofuran-d8 and performing NMR measurement.

[0100] 1) This method is used when an aqueous dispersion of a halogenated vinyl copolymer is available.

[0101] 10 ml of the aqueous dispersion of the halogenated vinyl copolymer was freeze-dried, and 0.5 g of the freeze-dried product was collected. The collected freeze-dried product was dissolved in 10 ml of tetrahydrofuran with a purity of 99.9 wt% or more, and 40 ml of methanol was added dropwise to the obtained solution. The generated precipitate was filtered, and the insoluble components remaining after filtration were collected.

[0102] The collected insoluble components were used as measurement samples.

[0103] 2) This method is used when an aqueous dispersion of a halogenated vinyl copolymer is not available and only a film coated with the aqueous dispersion is available.

[0104] The halogenated ethylene copolymer was separated from the membrane coated with the halogenated ethylene copolymer, and 0.5 g was collected and completely dissolved in 10 ml of tetrahydrofuran having a purity of 99.9 wt % or more. If it was not dissolved at room temperature, it was heated to 60° C. or below to completely dissolve it. 40 ml of methanol was added dropwise to the solution, the generated precipitate was filtered, and the insoluble component remaining after filtration was collected. The collected insoluble component was used as a measurement sample.

[0105] As a method for separating the halogenated vinyl copolymer from a membrane coated with the halogenated vinyl copolymer, when the following methods (A) to (C) can be performed, these methods are used. When (A) can be performed, (A) is used; when (A) is difficult to perform and (B) is performed, (B) is used; when (A) and (B) are difficult to perform and (C) is performed, (C) is used. When (A) to (C) are all difficult to perform and there are other means for separation, the other means is used. In this case, it is preferred to wash and dry so that the content of impurities other than the halogenated vinyl copolymer in the separated product is as small as possible. The mass ratio of the above impurities is preferably 0.5wt% or less in the measured sample. As conditions for the drying treatment, the temperature is set to 60°C or less and the treatment time is set to 10 hours or less. The impurities here refer to the components that are not contained in the aqueous dispersion of the halogenated vinyl copolymer before coating, such as the primer and solvent mixed in, and do not include additives such as emulsifiers added to the aqueous dispersion from the beginning. The amount of emulsifier in the separated product can be measured by the following process. i) Let the mass of the dried separated product be W1. ii) Wash the separated product with a large amount of pure water of 50 times or more in mass. Be careful not to let the polymer flow out. iii) Dry the separated product after washing and set its mass as W2. iv) Calculate the mass of the emulsifier from W1-W2.

[0106] (A) Physically peeling or cutting using tweezers or the like.

[0107] (B) Chemical separation is performed by using a solvent that does not dissolve the halogenated vinyl copolymer but dissolves the primer, preferably acetone.

[0108] (C) The ethylene halogenated copolymer is separated by eluting the ethylene halogenated copolymer using a membrane solvent that dissolves the ethylene halogenated copolymer but does not dissolve the substrate, and then drying the membrane.

[0109] When a solvent is used for separation by the methods (B) and (C), the halogenated vinyl copolymer is dried in a drying furnace or the like within a range where the halogenated vinyl copolymer does not decompose, and the measurement is performed after confirming that the weight of the solvent in the separated product is 0.5 wt % or less. Regarding the drying conditions, the temperature is set to be 50° C. or less, the drying time is set to be 10 hours or less, and the drying is performed under reduced pressure if necessary.

[0110] The measurement conditions of NMR are as follows.

[0111] Equipment: JEOL RESONANCE ECS400 (1H), Bruker Biospin Avance600 (13C)

[0112] Observed nuclei: 1H (399.78MHz), 13C (150.91MHz)

[0113] Pulse program: single pulse (1H), zgig30 (13C)

[0114] Integration times: 256 times (1H), 10000 times (13C)

[0115] Lock solvent: THF-d8

[0116] Chemical shift standard: THF (1H: 180 ppm, 13C: 67.38 ppm)

[0117] The monomers were assigned using the obtained NMR spectrum, and the components in the copolymer were identified by integrating the peaks.

[0118] As an example, in the case of a polymer containing structural units derived from vinylidene chloride, methacrylonitrile, methyl methacrylate, and acrylic acid, in the 13C-NMR spectrum, the content of structural units derived from vinylidene chloride is calculated by integrating 80 to 90 ppm, the content of structural units derived from methacrylonitrile is calculated by integrating 110 to 130 ppm, the content of structural units derived from methyl methacrylate is calculated by integrating 170 to 180 ppm, and the content of structural units derived from acrylic acid is calculated by integrating 180 to 200 ppm, and the constituent ratio of each monomer in the whole is calculated.

[0119] In the calculation of the above-mentioned composition ratio, in order to find out the amount of methyl methacrylate, the peak of the COOCH3 group (a in the following formula) is integrated. Methyl acrylate is also included as a monomer having a COOCH3 group and being a monomer that copolymerizes well with vinylidene chloride. When distinguishing the two, in the spectrum of 1HNMR, the presence or absence of the peak of the methyl group (b in the following formula) bonded to the main chain carbon to which the COOCH3 group is bonded is judged. The main chain carbon to which the methyl group is bonded does not combine with hydrogen, so the peak will not split, and the peak position is about 2ppm. In the case where a monomer having a methyl group, such as methacrylonitrile, is added in addition to methyl methacrylate, it can be judged based on the number of methyl peaks near 2ppm being multiple.

[0120] [Chemistry 1]

[0121]

[0122] Similarly, acrylonitrile and methacrylonitrile are distinguished by the presence or absence of the peak of the methyl group (b in the above formula).

[0123] If necessary, the above-mentioned insoluble fractions may be subjected to additional two-dimensional NMR measurement, infrared spectroscopy, etc., to identify the monomers. Alternatively, a copolymer with a known composition may be polymerized and measured by the same method for comparison.

[0124] (Characteristics of aqueous dispersion)

[0125] The maximum melting peak temperature (maximum melting point) and melting peak area of ​​the aqueous dispersion of the halogenated vinyl copolymer can be evaluated using a sample prepared by either of the following two methods (i) and (ii). The maximum melting peak temperature is preferably 170°C or less, particularly preferably 160°C or less.

[0126] When the area of ​​the melting peak with a melting peak temperature of 170°C or higher of the aqueous dispersion of the above-mentioned halogenated vinyl copolymer is set as S1, and the area of ​​the melting peak with a melting peak temperature of less than 170°C is set as S2, S1 / (S1+S2) is preferably greater than 0 and less than 0.33, particularly preferably less than 0.31, and further preferably less than 0.26.

[0127] (i) This method is used in the case where an aqueous dispersion of a halogenated ethylene copolymer can be obtained.

[0128] The aqueous dispersion of the halogenated vinyl copolymer was applied at a dry coating weight of 10 g / m 2 The film was coated on an aluminum plate using a Mayer bar and dried in an oven maintained at 100°C for 1 minute. The dried film was peeled off with tweezers within 5 minutes to collect a single film of the halogenated vinyl copolymer. 5 mg was collected from the single film and used for measurement.

[0129] In addition, when an additive such as a crystal nucleating agent is added to the water dispersion, a sample is prepared using the water dispersion in a state in which the additive is added, and the measurement is performed.

[0130] (ii) This method is used when an aqueous dispersion of a halogenated vinyl copolymer cannot be obtained and only a film coated with the aqueous dispersion can be obtained.

[0131] The halogenated vinyl copolymer was separated from the membrane coated with the halogenated vinyl copolymer, and 5 mg was collected for measurement.

[0132] As a method for separating the halogenated vinyl copolymer from a membrane coated with the halogenated vinyl copolymer, when the following methods (A) to (C) can be performed, these methods are used. When (A) can be performed, (A) is used; when (A) is difficult to perform and (B) is performed, (B) is used; when (A) and (B) are difficult to perform and (C) is performed, (C) is used. When (A) to (C) are all difficult to perform and there are other means for separation, the other means is used. In this case, it is preferred to wash and dry so that the content of impurities other than the halogenated vinyl copolymer in the separated product is as small as possible. The mass ratio of the above impurities is preferably 0.5wt% or less in the measured sample. As conditions for the drying treatment, the temperature is set to 60°C or less and the treatment time is set to 10 hours or less. The impurities here refer to the components that are not contained in the aqueous dispersion of the halogenated vinyl copolymer before coating, such as the primer and solvent mixed in, and do not include additives such as emulsifiers added to the aqueous dispersion from the beginning. The amount of emulsifier in the separated product can be measured by the following process. i) Let the mass of the dried separated product be W1. ii) Wash the separated product with a large amount of pure water of 50 times or more in mass. Be careful not to let the polymer flow out. iii) Dry the separated product after washing and set its mass as W2. iv) Calculate the mass of the emulsifier from W1-W2.

[0133] (A) Physically peeling or cutting using tweezers or the like.

[0134] (B) Chemical separation is performed by using a solvent that does not dissolve the halogenated vinyl copolymer but dissolves the primer, preferably acetone.

[0135] (C) The ethylene halogenated copolymer is separated by eluting the ethylene halogenated copolymer using a membrane solvent that dissolves the ethylene halogenated copolymer but does not dissolve the substrate, and then drying the membrane.

[0136] When a solvent is used for separation by the methods (B) and (C), the halogenated vinyl copolymer is dried in a drying furnace or the like within a range where the halogenated vinyl copolymer does not decompose, and the measurement is performed after confirming that the weight of the solvent in the separated product is 0.5 wt % or less. Regarding the drying conditions, the temperature is set to be 50° C. or less, the drying time is set to be 10 hours or less, and the drying is performed under reduced pressure if necessary.

[0137] The sample collected by the above method was heated to 170°C at 10°C / min in a nitrogen atmosphere using a differential scanning calorimeter Q-2000 manufactured by TA Instruments, and cooled to -40°C at 10°C / min. Then, it was heated to 190°C at 10°C / min, and the measurement data up to 190°C were obtained. Among the measurement data obtained up to 190°C, since vinylidene chloride begins to decompose at 180°C or above, the data above 180°C were not used, and the maximum melting peak temperature was calculated using the measurement values ​​from -40°C to 180°C during the second heating.

[0138] In this measurement, aluminum Tzero Pan and Tzero hermetic lid (manufactured by TAinstruments) were used as sample pans, and an empty pan of the pan was used as a reference. That is, the maximum melting peak temperature was calculated based on the value obtained by subtracting the empty pan measurement result from the sample measurement result.

[0139] Next, a baseline was derived by the method described below, and the area of ​​the melting peak below 170°C was calculated using Integrate Peak Linear in the Q-2000 analysis tool TAUniversalAnalysis, and this was taken as S2. When there is no melting peak below 170°C, S2 is 0.

[0140] The baseline was extracted by the method described below, and the area of ​​the melting peak at 170°C or higher was calculated using Integrate Peak Linear in the Q-2000 analysis tool TAUniversal Analysis, and this was defined as S1. When there was no melting peak at 170°C or higher, S1 was 0.

[0141] In the obtained values ​​of S1 and S2, the second decimal place is rounded off.

[0142] The baselines may not be on the same straight line. Such an example is described in the literature (Inorganic Materials, vol. 3, Jul. 271-283 (1996). For reference, the above literature Figure 6 (a) Shown in Figure 1 .

[0143] Several examples of methods for drawing a baseline can be cited. In the case of multiple peaks, a baseline is drawn for each peak to calculate the area. It should be noted that in the following cases, when multiple tangents are drawn, the tangent with the largest absolute value of the slope is used as the tangent of the curve.

[0144] (I): When a tangent line is drawn between the peak and the positive and negative curves ( Figure 2 ) and use the tangent lines to the curves on the positive and negative sides as the baselines.

[0145] (II): In the case not belonging to (I) and the peak is sandwiched by lines parallel to the horizontal axis on both the positive and negative sides of the peak ( Figure 3 , 4 ), a line connecting points where the endothermic peaks on the positive and negative sides are no longer parallel to the horizontal axis (points that tilt positively or negatively) is used as the baseline.

[0146] (III): In the case that it does not belong to (I) or (II) and one of the positive side and the negative side of the peak is a line parallel to the horizontal axis and the other is a curve ( Figure 5 ), take the point where the line parallel to the horizontal axis is no longer parallel to the horizontal axis as the starting point, and draw a tangent line to the other side of the curve as the baseline.

[0147] (IV): In the case where the peak does not belong to any of the cases (I), (II), and (III) and the positive side of the peak is cut off due to the upper limit of measurement of 180°C ( Figure 6 ), with the point at 180°C as the starting point, a tangent line is drawn to the negative side of the peak as the baseline. It should be noted that when the negative side of the peak is a line parallel to the horizontal axis, the line connecting the above starting point and the point not parallel to the horizontal axis can be used as the baseline.

[0148] As an example, find Figure 7 The area of ​​the spectrum. Only the endothermic curve of the second heating is shown. In this example, S1 is 3.2 J / g and S2 is 6.3 J / g.

[0149] (Method for producing aqueous dispersion)

[0150] The aqueous dispersion of the halogenated vinyl copolymer of the present embodiment can be produced by emulsion polymerization of the monomer mixture. Although not particularly limited, the emulsion polymerization is usually carried out at a temperature of 30 to 70° C. The polymerization temperature is preferably in the range of 40 to 60° C. By setting the polymerization temperature to 70° C. or less, the decomposition of the raw materials during the polymerization can be suppressed, which is preferred. By setting the polymerization temperature to 30° C. or more, the polymerization rate can be increased, so the polymerization efficiency is good.

[0151] The above-mentioned vinyl halide copolymer is a copolymer containing a comonomer having a reactivity ratio r1 of less than 0.7 relative to vinylidene chloride (i.e., a monomer that is not easily reactive with vinylidene chloride) and a vinyl halide monomer, so in the reactor, the comonomer having a reactivity ratio r1 of less than 0.7 is consumed preferentially over the vinyl halide monomer. Therefore, in the case where unreacted monomers accumulate in the reaction, the unreacted monomers become mixed monomers having more vinyl halide monomers than the feed amount. Thus, a block having a large amount of vinyl halide monomers is formed in the copolymer in the final stage of polymerization, and the vinyl halide copolymer has a high melting point. In significant cases, the generated copolymer has two melting peaks, and the more blocks of vinyl halide monomers are formed, the more the melting peak area above 170°C increases.

[0152] In an aqueous dispersion having many blocks containing a large amount of vinyl halide monomer, film formation defects due to crystallization starting from the blocks are likely to occur during long-term storage.

[0153] Therefore, in order to improve the film-forming property after long-term storage, it is important to polymerize a copolymer having a small melting peak area at 170° C. or higher, that is, a small amount of blocks having a large amount of vinyl halide monomers.

[0154] The method for controlling the area of ​​the melting peak at 170° C. or higher of the halogenated vinyl copolymer is not particularly limited, and as examples, any of the following methods may be used, or a combination of a plurality of methods may be used.

[0155] Method for controlling the area of ​​the melting peak above 170°C-1

[0156] The vinyl halide monomer and the comonomer with a reactivity ratio r1 of less than 0.7 used in the emulsion polymerization of the aqueous dispersion of the vinyl halide copolymer of the present embodiment can be mixed in a specific amount before the polymerization, for example, and can be added continuously or in batches in stages. In the case of continuous or staged addition, the amount of the vinyl halide monomer and the comonomer with a reactivity ratio r1 of less than 0.7 added per hour is preferably not higher than the amount of the vinyl halide monomer and the comonomer with a reactivity ratio r1 of less than 0.7 consumed in the polymerization per hour, and is preferably 95% by mass or less of the total amount of the vinyl halide monomer and the comonomer with a reactivity ratio r1 of less than 0.7 consumed in the polymerization per hour, more preferably 90% by mass or less, and further preferably 85% by mass or less.

[0157] As an example, when the polymerization temperature is 50°C, it is preferred to add 80 parts by mass of the monomer raw material for 20 hours or more, particularly preferably for 25 hours or more, and further preferably for 30 hours or more relative to the total mass of 100 parts by mass of the added vinyl halide monomer and the comonomer with a reactivity ratio r1 less than 0.7. The time for continuous or staged addition is preferably optimized according to the polymerization temperature. A preferred method is to add the monomer in batches at the beginning of the polymerization and then continuously add the remainder. For example, at the beginning of the polymerization, 1 to 30 parts by mass of vinyl halide monomer and comonomer with a reactivity ratio r1 less than 0.7 can be added relative to 100 parts by mass of the total mass of the vinyl halide monomer and the comonomer with a reactivity ratio r1 less than 0.7 contained in the raw material monomer, and then the vinyl halide monomer and the comonomer with a reactivity ratio r1 less than 0.7 in the above preferred ratio are added every hour. By continuously adding the monomer at the above speed, the accumulation of unreacted monomers in the reactor can be reduced, and as a result, the melting peak area of ​​the copolymer above 170°C can be reduced.

[0158] Method for controlling the area of ​​the melting peak above 170°C-2

[0159] The total amount of the polymerization initiator added during the polymerization is preferably 0.015 parts by mass or more, more preferably 0.04 parts by mass or more, and particularly preferably 0.08 parts by mass or more, based on 100 parts by mass of the halogenated vinyl copolymer. By adding the total amount of the polymerization initiator within the above range, the accumulation of unreacted monomers in the reactor can be reduced, and as a result, the melting peak area of ​​the copolymer at 170° C. or more can be reduced.

[0160] In addition, the polymerization initiator is preferably continuously added over a period longer than the period for continuously adding the monomers.

[0161] Furthermore, it is preferred to add a polymerization activator which accelerates the radical decomposition of the initiator.

[0162] Method for controlling the area of ​​the melting peak above 170°C-3

[0163] In the emulsion polymerization of the vinyl halide copolymer, after the continuous addition of the monomers is completed and until the internal pressure decreases, the addition of the initiator, polymerization activator and / or emulsifier may be continued, but the addition is preferably completed before the internal pressure decreases. By completing the polymerization before the internal pressure decreases, the unreacted monomers including a large amount of vinyl halide monomers accumulated in the reactor can be kept in an unreacted state, and as a result, the melting peak area of ​​the copolymer at 170° C. or above can be reduced.

[0164] Method for controlling the area of ​​the melting peak above 170°C -4

[0165] Reduce the proportion of halogenated vinyl monomers in the raw material monomers.

[0166] By reducing the ratio of the vinyl halide monomer, the accumulated amount of the vinyl halide monomer at the end of the polymerization can be reduced, and as a result, the melting peak area of ​​the copolymer at 170° C. or higher can be reduced.

[0167] Examples of surfactants that can be used for the emulsion polymerization of the aqueous dispersion of the halogenated vinyl copolymer include anionic surfactants such as alkyl sulfate ester salts, alkylbenzene sulfonates, alkyl sulfosuccinates, alkyl diphenyl ether disulfonates, and alkyl sulfonates.

[0168] Examples of the polymerization initiator include persulfates such as sodium persulfate and potassium persulfate, hydrogen peroxide, tert-butyl hydroperoxide, and peroxides such as cumene hydroperoxide, etc. Tert-butyl hydroperoxide is preferred.

[0169] As the polymerization activator, for example, it is preferable to add a polymerization activator that accelerates the radical decomposition of the initiator, such as sodium hydrogen sulfite or sodium D-arabinose ascorbate.

[0170] These polymerization additives are not particularly limited, and may be, for example, those conventionally and preferably used in the technical field.

[0171] The ethylene halogenated copolymer particles contained in the aqueous dispersion of the ethylene halogenated copolymer of the present embodiment are not particularly limited, but the average particle size thereof is preferably 10 to 1000 nm. When the average particle size is within this range, the storage stability of the aqueous dispersion is good and the coating property is improved.

[0172] The solid content of the aqueous dispersion of the ethylene halide copolymer according to the present embodiment is not particularly limited, but is usually 10 to 70% by mass.

[0173] It is preferred to add a crystal nucleating agent to the aqueous dispersion of the halogenated vinyl copolymer of the present embodiment. The crystal nucleating agent is an additive that promotes crystallization of a film obtained by forming the aqueous dispersion into a film, and any known additive that promotes crystallization of a resin can be used.

[0174] Examples of such additives include metal salts of phosphate esters, metal salts of benzoates, metal salts of pimelic acid, metal salts of rosin, benzylidene sorbitol, quinacridone, cyanine blue, metal salts of oxalates, metal salts of stearates, ionomers, high melting point PET, carbon black, metal oxides, metal sulfates, kaolin, clay, high melting point polyamides, crystalline resins having a composition different from that of the above-mentioned halogenated vinyl copolymer of the present embodiment, silicon oxide, titanium oxide, wax, highly crystalline halogenated vinyl copolymer particles different from the above-mentioned halogenated vinyl copolymer of the present embodiment, and the like. One or more of them may be used in combination.

[0175] Silica, titanium oxide, wax, and highly crystalline halogenated ethylene copolymer particles are preferred, and wax and highly crystalline halogenated ethylene copolymer particles are particularly preferred.

[0176] The amount of the crystal nucleating agent added is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, further preferably 5 parts by mass or less, and particularly preferably 2 parts by mass or less, relative to 100 parts by mass of the halogenated vinyl copolymer. The amount of the crystal nucleating agent added is preferably 0.05 parts by mass or more.

[0177] When two or more crystal nucleating agents are added, the total amount is used.

[0178] The term "wax" is understood in this specification to mean any natural wax or synthetic wax, and further includes wood wax, lacquer wax, sugar cane wax, palm wax, candelilla wax, jojoba oil, pearl wax, spermaceti wax, worm wax, wool wax, FT wax, paraffin wax, microcrystalline wax, carnauba wax, beeswax, Chinese worm wax, ozokerite, polyolefin wax and montan wax, and their esters, but not limited to these.

[0179] The highly crystalline halogenated vinyl copolymer particles have a melting peak area ratio S1 / (S1+S2) greater than 0.33. In addition, the maximum melting peak temperature is 160°C or higher, particularly preferably 170°C or higher. Here, the maximum melting peak temperature is measured according to the above-mentioned melting peak measurement method, and a maximum peak temperature of 180°C or lower is used.

[0180] The highly crystalline vinyl halide copolymer particles are preferably vinylidene chloride copolymer particles, and particularly preferably vinylidene chloride copolymer particles in which 91 parts by mass or more of vinylidene chloride is copolymerized per 100 parts by mass of the vinylidene chloride copolymer.

[0181] By adding these crystal nucleating agents, the crystallization after film formation can be promoted, and the coating film can exhibit high water vapor barrier properties.

[0182] In addition, the aqueous dispersion of the halogenated vinyl copolymer of the present embodiment may be added with various commonly used ingredients as needed, such as defoamers, rheology modifiers, thickeners, dispersants, stabilizers such as surfactants, wetting agents, plasticizers, colorants, silicone oils, etc. In addition, the aqueous dispersion may also be mixed with light stabilizers, ultraviolet absorbers, silane coupling agents, inorganic fillers, coloring pigments, extender pigments, etc. as needed for use.

[0183] The solvent of the aqueous dispersion of the halogenated vinyl copolymer of the present embodiment may be water alone or may contain water and other solvents (such as alcohols, acetone, etc.). When other solvents are contained, the amount is preferably 10 parts by mass or less relative to 100 parts by mass of water.

[0184] The aqueous dispersion of the halogenated vinyl copolymer of the present embodiment can be used as a coating material for films for blister packages and the like.

[0185] [membrane]

[0186] The film of the present embodiment has a layer coated with the aqueous dispersion of the ethylene halogenated copolymer of the present embodiment. The layer contains at least the ethylene halogenated copolymer and may be a layer consisting only of the ethylene halogenated copolymer.

[0187] The film of the present embodiment preferably has a layer on which the aqueous dispersion of the halogenated vinyl copolymer of the present embodiment is coated on a film substrate. The film substrate is not particularly limited, and representative examples include films made of polyvinyl chloride, polyester, polyamide, and polypropylene. The most commonly used is a film made of polyvinyl chloride. The thickness of the film substrate varies depending on the material used, and can generally be 8 to 300 μm.

[0188] The layer coated with the aqueous dispersion of the halogenated vinyl copolymer is not particularly limited, and can be, for example, coated with a coating weight of 1 g / m 2 ~200g / m 2 In the range of 20 g / m 2 ~100g / m 2 to be formed within the scope of the method.

[0189] In addition, in the film of the present embodiment, in addition to the layer coated with the aqueous dispersion of the ethylene halide copolymer, a layer of a copolymer mainly composed of a monomer rich in polymerization activity other than ethylene halide and adjusted in functionality may be optionally included. As such a layer, for example, a primer layer may be formed on a film substrate using an aqueous resin emulsion or an acrylic dispersion, and a layer coated with the aqueous dispersion of the ethylene halide copolymer of the present embodiment may be provided thereon.

[0190] The aqueous dispersion of the vinyl halide copolymer of the present embodiment is preferably applied onto the film substrate as exemplified above and used as a blister package. The obtained blister package exhibits excellent barrier properties (for example, water vapor barrier properties).

[0191] Furthermore, the film of the present embodiment can be used as a coating agent to form a transparent coating film as it is, in addition to being suitable for blister packaging.

[0192] As a method for coating the aqueous dispersion of the halogenated vinyl copolymer of the present embodiment on the film substrate, a known method such as air spraying, airless coating, roll coating, curtain coating, roll coating, dip coating, spin coating, etc. can be used for the surface of the object to be coated. Usually, after coating on the film substrate, it is kept at room temperature or under heating for a specific time to dry.

[0193] The water vapor barrier properties and film-forming properties after long-term storage of the aqueous dispersion of the halogenated vinyl copolymer according to the present embodiment and the film having a layer coated with the aqueous dispersion can be evaluated using the following parameters (1) and (2).

[0194] (1) Water vapor barrier properties

[0195] The water vapor barrier property of the film having a layer coated with the aqueous dispersion of the halogenated vinyl copolymer of the present embodiment can be evaluated under the conditions of 38° C. and 100% RH using a water vapor transmission rate measuring apparatus PERMATRAN 3 / 33 manufactured by MOCON Co. (unit: g / m 2 day at 38°C, 100% RH).

[0196] The average value of the measured values ​​from 48 hr to 60 hr after the start of the measurement was taken as the water vapor transmission rate.

[0197] The measurement was performed 4 times, and the average value was used.

[0198] Although not particularly limited, the water vapor barrier is preferably 0.1 to 10 g / m 2 · About a day, the upper limit for general pharmaceutical packaging (coating amount 80GSM) is 1.0g / m 2 · About 0.6g / m2 is preferred for pharmaceutical packaging that requires high barrier properties. 2 The film having a layer coated with the aqueous dispersion of the halogenated vinyl copolymer of this embodiment can be used for applications requiring high barrier properties (such as water vapor barrier properties), and the preferred numerical range of the water vapor permeability is 0.6 g / m 2 ·Day or less, more preferably 0.5g / m 2 ·Day or less, more preferably 0.4g / m 2 ·Day or less.

[0199] (2) Film-forming properties after long-term storage (film-forming life)

[0200] In a constant temperature and humidity chamber at 23°C and 55% humidity, 45 ml of water dispersion was collected in a 50 ml sample bottle, covered and left to stand for 5 hours. Then, in the constant temperature and humidity chamber, the thermal gradient tester (BIG HEART) manufactured by Imoto Manufacturing was adjusted to 10°C at one end and 30°C at the other end. After confirming that the thermal gradient on the tester reached 1°C per 4 cm, the water dispersion was applied on the tester using a 0.2 mm applicator and dried for 12 hours. The highest temperature at which cracks with a diameter of more than 1 mm were generated on the coating was taken as the minimum film forming temperature (MFT). MFT was measured 10 times for one sample, and the average value was used.

[0201] The prepared aqueous dispersion was stored at 23°C, and the MFT was measured every one month. When the MFT of the 0th month was T0 and the MFT of the nth month was Tn, the change in MFT ΔMFT was calculated from Tn-T0. At the time n when ΔMFT≧4°C was satisfied, the film-forming property was considered to be impaired, and the time when ΔMFT≧4°C was satisfied for the first time was taken as the limit of the film-forming property after long-term storage (film-forming life).

[0202] For example, when the MFT is 12° C. in the 0th month, 13° C. in the 1st month, and 16° C. in the 2nd month, the film-forming life of the aqueous dispersion is 2 months.

[0203] After this film-forming life, a uniform coating film cannot be obtained, and the coating film cannot exhibit sufficient water vapor barrier properties.

[0204] Aqueous dispersions with short film-forming life are difficult to circulate and store, so the longer the film-forming life, the better. Usually, when the aqueous dispersion is circulated and stored, the film-forming life is preferably 3 months or more, more preferably 4 months or more, further preferably 5 months or more, and further preferably 7 months or more.

[0205] Example

[0206] The present invention is described in more detail below by way of examples.

[0207] In addition, the parts and % in Examples and Comparative Examples represent parts by mass and % by mass, respectively.

[0208] <Polymerization Example of Aqueous Dispersion>

[0209] [Example 1]

[0210] In a pressure-resistant reactor with a glass lining, 57 parts of pure water, 0.03 parts of sodium D-arabinose ascorbate, and 0.2 parts of sodium alkyl sulfonate were added to 100 parts of the total weight of the monomers, and after degassing under stirring, the temperature of the contents was maintained at 45°C. In another container, a raw material monomer mixture with a mass composition ratio of VDC / MAN / MMA / AA=91.5 / 5.2 / 2.4 / 0.9 was prepared. 20 parts of the raw material monomer mixture were added to the above pressure-resistant reactor at one time, and polymerization was carried out until the internal pressure decreased. Then, the remaining 80 parts of the monomer mixture were continuously and quantitatively pressed in.

[0211] In parallel, an initiator prepared by dissolving 0.04 parts of tert-butyl hydroperoxide in 3.5 parts of pure water, a reducing agent prepared by dissolving 0.015 parts of sodium D-arabinose ascorbate in 3.5 parts of pure water, and an emulsifier prepared by dissolving 1.6 parts of sodium alkyl diphenyl ether disulfonate in 2.5 parts of pure water were continuously and quantitatively injected. During this time, the contents were stirred and maintained at 45° C., and the reaction was carried out until the internal pressure was sufficiently reduced.

[0212] The polymerization yield was 99.9%. Since the polymerization yield was approximately 100%, the composition of the copolymer was approximately the same as the raw material charge ratio. The water dispersion thus obtained was stripped by steam to remove unreacted monomers, and the solid content was adjusted to 50-60%.

[0213] In this polymerization, 80 parts of the monomer mixture was continuously introduced under pressure, and the time until the total amount was introduced was 21 hours.

[0214] [Comparative Example 1]

[0215] In the same manner as in Example 1 of Patent Document 4, an aqueous dispersion of a vinylidene chloride copolymer was prepared.

[0216] In a pressure-resistant reactor with a glass lining, 57 parts of pure water, 0.03 parts of sodium D-arabinose ascorbate, and 0.2 parts of sodium alkyl sulfonate were added to 100 parts of the total weight of the monomers, and after degassing under stirring, the temperature of the contents was maintained at 45°C. In another container, a raw material monomer mixture with a mass composition ratio of VDC / MMA / AN=90.1 / 9.4 / 0.5 was prepared. 20 parts of the raw material monomer mixture were added to the above-mentioned pressure-resistant reactor at one time, and polymerization was carried out until the internal pressure decreased. Then, the remaining 80 parts of the monomer mixture were continuously and quantitatively pressed.

[0217] In parallel, an initiator prepared by dissolving 0.014 parts of tert-butyl hydroperoxide in 3.5 parts of pure water, a reducing agent prepared by dissolving 0.015 parts of sodium D-arabinose ascorbate in 3.5 parts of pure water, and an emulsifier prepared by dissolving 1.6 parts of sodium alkyl diphenyl ether disulfonate in 2.5 parts of pure water were continuously and quantitatively injected. During this time, the contents were stirred and maintained at 45° C., and the reaction was carried out until the internal pressure was sufficiently reduced.

[0218] The polymerization yield was 99.9%. Since the polymerization yield was approximately 100%, the composition of the copolymer was approximately the same as the raw material charge ratio. The water dispersion thus obtained was stripped by steam to remove unreacted monomers, and the solid content was adjusted to 50-60%.

[0219] In this polymerization, 80 parts of the monomer mixture was continuously fed under pressure, and the time until the total amount was fed was 21 hours.

[0220] [Comparative Example 2]

[0221] In the same manner as in Example 4 of Patent Document 4, an aqueous dispersion of a vinylidene chloride copolymer was prepared.

[0222] Polymerization was carried out in the same manner as in Comparative Example 1 except that the mass composition ratio of the raw material monomer mixture was VDC / MMA / MAN / AA=92.0 / 6.5 / 1.0 / 0.5.

[0223] The polymerization yield was 99.9%. Since the polymerization yield was approximately 100%, the composition of the copolymer was approximately the same as the raw material charge ratio. The water dispersion thus obtained was stripped by steam to remove unreacted monomers, and the solid content was adjusted to 50-60%.

[0224] [Comparative Example 3]

[0225] In the same manner as in Comparative Example 1 of Patent Document 4, an aqueous dispersion of a vinylidene chloride copolymer was prepared.

[0226] The polymerization was carried out in the same manner as in Comparative Example 1 except that the mass composition ratio of the raw material monomer mixture was VDC / MAN / MMA / AA=91.5 / 5.2 / 2.4 / 0.9. The polymerization yield was 99.9%. Since the polymerization yield was approximately 100%, the composition of the copolymer was approximately the same as the raw material charge ratio. The water dispersion thus obtained was stripped by steam to remove unreacted monomers, and the solid content was adjusted to 50 to 60%.

[0227] [Comparative Example 4]

[0228] In the same manner as in Example 7 of Patent Document 1, an aqueous dispersion of a vinylidene chloride copolymer was prepared.

[0229] 100 parts of ion exchange water, 0.2 parts of sodium dodecyl sulfate, and 0.2 parts of sodium persulfate were placed in a pressure-resistant reactor with a glass lining, and after degassing, the temperature of the contents was maintained at 50°C. 92.2 parts by mass of vinylidene chloride (VDC), 7.5 parts by mass of methyl acrylate (MA), and 0.3 parts by mass of acrylic acid (AA) were weighed and mixed in another container to prepare a monomer mixture. 10 parts by mass of the monomer mixture was added to the reactor, and after reacting for about 10 hours, the remaining 90 parts by mass of the monomer mixture and 0.7 parts by mass of sodium dodecyl sulfate were added in full while adjusting the internal temperature to 23 hours so as not to increase, and then reacted until the internal pressure dropped to 0.1 MPa, and then heated to 60°C, and the residual monomers were removed under reduced pressure to obtain an aqueous dispersion.

[0230] [Comparative Example 5]

[0231] In the same manner as in Example 11 of Patent Document 1, an aqueous dispersion of a vinylidene chloride copolymer was prepared.

[0232] 100 parts of ion exchange water, 0.2 parts of sodium dodecyl sulfate, and 0.2 parts of sodium persulfate were placed in a pressure-resistant reactor with a glass lining, and after degassing, the temperature of the contents was maintained at 50°C. 91.5 parts by mass of vinylidene chloride (VDC), 8.2 parts by mass of methyl acrylate (MA), and 0.3 parts by mass of acrylic acid (AA) were weighed and mixed in another container to prepare a monomer mixture. 10 parts by mass of the monomer mixture was added to the reactor, and after reacting for about 10 hours, the remaining 90 parts by mass of the monomer mixture and 0.7 parts by mass of sodium dodecyl sulfate were added in full while adjusting the internal temperature to 22 hours so as not to increase, and then reacted until the internal pressure dropped to 0.1 MPa, and then heated to 60°C, and the residual monomers were removed under reduced pressure to obtain an aqueous dispersion. To this aqueous dispersion was added 0.3 parts by mass of a polyethylene wax composition (Poligen (registered trademark) WE7 manufactured by BASF) based on 100 parts by mass of the vinylidene chloride copolymer in the aqueous dispersion to obtain an aqueous dispersion.

[0233] [Comparative Example 6]

[0234] In the same manner as in Comparative Example 3 of Patent Document 5, an aqueous dispersion of a vinylidene chloride copolymer was prepared.

[0235] 86 parts by mass of water, 0.15 parts by mass of sodium alkyl sulfonate (Bayer Wallolate U) and 0.10 parts by mass of sodium persulfate were placed in a pressure-resistant reactor with a glass lining, and the temperature of the contents was maintained at 55°C after degassing. 89 parts by mass of vinylidene chloride, 3 parts by mass of methacrylonitrile and 8 parts by mass of methyl methacrylate were weighed and mixed in a different container to prepare a monomer mixture. 10 parts by mass of the monomer mixture were placed in the above reactor, and the reaction was carried out under stirring. After confirming that the reaction was almost completed by reducing the internal pressure of the reactor, 10 parts by mass of sodium alkyl sulfonate in a 15% by mass aqueous solution was pressed into the reactor, and then the remaining total amount of the monomer mixture was continuously added quantitatively over 15 hours. The reaction was further carried out until the internal pressure was sufficiently reduced. A 15% by mass aqueous solution of sodium alkyl sulfonate was added to the aqueous dispersion obtained in this way so that the gas-liquid interfacial tension at 20 degrees was 42 mN / m.

[0236] [Example 2]

[0237] The polymerization was carried out in the same manner as in Example 1 except that the initiator was changed from a solution obtained by dissolving 0.04 parts of tert-butyl hydroperoxide in 3.5 parts of pure water to a solution obtained by dissolving 0.08 parts of tert-butyl hydroperoxide in 3.5 parts of pure water. The polymerization yield was 99.9%. Since the polymerization yield was approximately 100%, the composition of the copolymer was approximately the same as the raw material charge ratio. The water dispersion thus obtained was stripped by steam to remove unreacted monomers, and the solid content was adjusted to 50 to 60%.

[0238] [Example 3]

[0239] The polymerization was carried out in the same manner as in Comparative Example 3 except that 80 parts of the monomer mixture was continuously pressed in and the time until the total amount was added was 45 hours. The polymerization yield was 99.9%. Since the polymerization yield was approximately 100%, the composition of the copolymer was approximately the same as the raw material feed ratio. The water dispersion thus obtained was stripped by steam to remove unreacted monomers, and the solid content was adjusted to 50 to 60%.

[0240] [Example 4]

[0241] The polymerization was carried out in the same manner as in Example 1 except that the mass composition ratio of the raw material monomer mixture was VDC / MMA / MAN=89 / 8 / 3. The polymerization yield was 99.9%. Since the polymerization yield was approximately 100%, the composition of the copolymer was approximately the same as the raw material charge ratio. The water dispersion thus obtained was stripped by steam to remove unreacted monomers, and the solid content was adjusted to 50-60%.

[0242] [Example 5]

[0243] Polymerization was carried out in the same manner as in Example 4. A polyethylene wax composition (Poligen (registered trademark) WE7 manufactured by BASF Corporation) was added to the prepared aqueous dispersion in an amount of 1.0 part by mass based on the dry mass of 100 parts by mass of the vinylidene chloride copolymer.

[0244] [Example 6]

[0245] The polymerization was carried out in the same manner as in Comparative Example 1 except that the mass composition ratio of the raw monomer mixture was VDC / AN=98 / 2, and 1.0 part by mass of the aqueous dispersion of the obtained vinylidene chloride copolymer (crystallization nucleating agent) was added to 100 parts by mass of the dry mass of the vinylidene chloride copolymer prepared in Example 4.

[0246] It should be noted that the vinylidene chloride copolymer added as a crystal nucleating agent had only a melting peak at 170° C. or higher, and S1 / (S1+S2) was 1.0.

[0247] The maximum melting peak of the added vinylidene chloride copolymer was 175°C.

[0248] [Example 7]

[0249] The polymerization was carried out in the same manner as in Example 1 except that the mass composition ratio of the raw material monomer mixture was VDC / MAN=85 / 15. The polymerization yield was 99.9%. Since the polymerization yield was approximately 100%, the composition of the copolymer was approximately the same as the raw material charge ratio. The water dispersion thus obtained was stripped by steam to remove unreacted monomers, and the solid content was adjusted to 50-60%.

[0250] [Example 8]

[0251] The polymerization was carried out in the same manner as in Example 1 except that the mass composition ratio of the raw material monomer mixture was VDC / MAN=80 / 20. The polymerization yield was 99.9%. Since the polymerization yield was approximately 100%, the composition of the copolymer was approximately the same as the raw material charge ratio. The water dispersion thus obtained was stripped by steam to remove unreacted monomers, and the solid content was adjusted to 50-60%.

[0252] [Example 9]

[0253] Polymerization was carried out in the same manner as in Example 7. A montanic acid wax composition (T-350A manufactured by Saiden Chemical Co., Ltd.) was added to the prepared aqueous dispersion in an amount of 1.0 part by mass based on the dry mass of 100 parts by mass of the vinylidene chloride copolymer.

[0254] [Example 10]

[0255] Polymerization was performed in the same manner as in Example 8. A carnauba wax composition (ML160RPH manufactured by Michelman Co., Ltd.) was added to the prepared aqueous dispersion in an amount of 1.0 part by mass based on the dry mass of 100 parts by mass of the vinylidene chloride copolymer.

[0256] [Example 11]

[0257] A water dispersion was prepared in the same manner as in Example 6 except that the amount of the water dispersion of the vinylidene chloride copolymer added as a crystal nucleating agent was changed to 5.0 parts by mass in terms of dry mass.

[0258] [Example 12]

[0259] A water dispersion was prepared in the same manner as in Example 6 except that the amount of the water dispersion of the vinylidene chloride copolymer added as a crystal nucleating agent was 10.0 parts by mass in terms of dry mass.

[0260] [Example 13]

[0261] A water dispersion was prepared in the same manner as in Example 6 except that the amount of the water dispersion of the vinylidene chloride copolymer added as a crystal nucleating agent was changed to 20.0 parts by mass in terms of dry mass.

[0262] [Comparative Example 7]

[0263] A water dispersion was prepared in the same manner as in Example 6 except that the amount of the water dispersion of the vinylidene chloride copolymer added as a crystal nucleating agent was changed to 30.0 parts by mass in terms of dry mass.

[0264] [Example 14]

[0265] The polymerization was carried out in the same manner as in Example 1 except that the mass composition ratio of the raw material monomer mixture was VDC / AN / MMA=90 / 1.5 / 8.5. The polymerization yield was 99.9%. Since the polymerization yield was approximately 100%, the composition of the copolymer was approximately the same as the raw material charge ratio. The water dispersion thus obtained was stripped by steam to remove unreacted monomers, and the solid content was adjusted to 50-60%.

[0266] [Example 15]

[0267] The polymerization was carried out in the same manner as in Example 1 except that the mass composition ratio of the raw material monomer mixture was VDC / MAN / MMA=86 / 5 / 9. The polymerization yield was 99.9%. Since the polymerization yield was approximately 100%, the composition of the copolymer was approximately the same as the raw material charge ratio. The water dispersion thus obtained was stripped by steam to remove unreacted monomers, and the solid content was adjusted to 50-60%.

[0268] [Example 16]

[0269] The polymerization was carried out in the same manner as in Example 1 except that the mass composition ratio of the raw material monomer mixture was VDC / MAN / MA=90 / 1 / 9. The polymerization yield was 99.9%. Since the polymerization yield was approximately 100%, the composition of the copolymer was approximately the same as the raw material charge ratio. The water dispersion thus obtained was stripped by steam to remove unreacted monomers, and the solid content was adjusted to 50-60%.

[0270] [Example 17]

[0271] The polymerization was carried out in the same manner as in Example 1 except that the mass composition ratio of the raw material monomer mixture was VDC / MAN / MA=90 / 3 / 7. The polymerization yield was 99.9%. Since the polymerization yield was approximately 100%, the composition of the copolymer was approximately the same as the raw material charge ratio. The water dispersion thus obtained was stripped by steam to remove unreacted monomers, and the solid content was adjusted to 50-60%.

[0272] [Example 18]

[0273] The polymerization was carried out in the same manner as in Example 1 except that the mass composition ratio of the raw material monomer mixture was VDC / MAN / MA=90 / 5 / 5. The polymerization yield was 99.9%. Since the polymerization yield was approximately 100%, the composition of the copolymer was approximately the same as the raw material charge ratio. The water dispersion thus obtained was stripped by steam to remove unreacted monomers, and the solid content was adjusted to 50-60%.

[0274] [Example 19]

[0275] The polymerization was carried out in the same manner as in Example 1 except that the mass composition ratio of the raw material monomer mixture was VDC / MMA=90 / 10. The polymerization yield was 99.9%. Since the polymerization yield was approximately 100%, the composition of the copolymer was approximately the same as the raw material charge ratio. The water dispersion thus obtained was stripped by steam to remove unreacted monomers, and the solid content was adjusted to 50-60%.

[0276] The following evaluations were performed using the obtained aqueous dispersion of the vinylidene chloride copolymer.

[0277] <Coating film production>

[0278] A Meyer bar was used on a stretched polyvinyl chloride film (thickness 250 μm) treated with corona discharge to obtain a coating weight of 2 g / m after drying. 2 The aqueous dispersion of the vinylidene chloride copolymer obtained in the example and the comparative example was dried once with a Meyer rod to a coating weight of 10 g / m 2 The film was coated with a coating method, dried in a hot air circulation dryer at 85°C for 15 seconds, and repeatedly coated until the coating mass after drying was 40g / m 2 The obtained coating film was stored in an oven at 40°C for 24 hours, and then humidity-controlled in a constant temperature and humidity chamber at 20°C and 55% for 2 hours.

[0279] <Water vapor transmission rate (moisture permeability) measurement>

[0280] The obtained coating film was measured under the conditions of 38°C and 100% RH using a water vapor transmission rate measuring device PERMATRAN 3 / 33 manufactured by MOCON (unit: g / m 2 day at 38°C, 100% RH).

[0281] The average value of the measured values ​​from 48 hr to 60 hr after the start of the measurement was taken as the water vapor transmission rate.

[0282] The measurement was performed 4 times, and the average value was used.

[0283] <Measurement of Maximum Peak Temperature of Melting>

[0284] The aqueous dispersion of the halogenated vinyl copolymer was coated at a dry coating weight of 10 g / m 2 The film was coated on an aluminum plate using a Meyer rod and dried in an oven maintained at 100°C for 1 minute. The dried film was peeled off with tweezers within 5 minutes to collect a separate film of the halogenated vinyl copolymer. 5 mg was collected from the separate film. It should be noted that when an additive such as a crystallization nucleating agent is added to the aqueous dispersion, a sample is prepared using the aqueous dispersion in a state where the additive is added and measured.

[0285] The sample collected by the above method was heated to 170° C. at 10° C. / min and cooled to −40° C. at 10° C. / min in a nitrogen atmosphere using a differential scanning calorimeter Q-2000 manufactured by TA Instruments.

[0286] Then, the mixture was heated to 190°C at a rate of 10°C / min, and the measured data up to 190°C were obtained. Of the measured data up to 190°C, since vinylidene chloride begins to decompose at 180°C or above, the data above 180°C were not used, and the maximum melting peak temperature was determined using the measured values ​​from -40°C to 180°C during the second heating.

[0287] In this measurement, aluminum Tzero Pan and Tzero hermetic lid (manufactured by TAinstruments) were used as sample pans, and an empty pan of the same pan was used as a reference.

[0288] Next, a baseline was derived by the method described below, and the area of ​​the melting peak below 170°C was calculated using Integrate Peak Linear in the Q-2000 analysis tool TAUniversalAnalysis, and this was taken as S2. When there is no melting peak below 170°C, S2 is 0.

[0289] The baseline was extracted, and the area of ​​the melting peak at 170°C or higher was calculated using Integrate Peak Linear in the Q-2000 analysis tool TAUniversal Analysis, and this was defined as S1. When there was no melting peak at 170°C or higher, S1 was 0.

[0290] In the obtained values ​​of S1 and S2, the second decimal place is rounded off.

[0291] <Film-forming property test after long-term storage>

[0292] In a constant temperature and humidity chamber at 23°C and 55% humidity, 45 ml of water dispersion was collected in a 50 ml sample bottle, covered and left to stand for 5 hours. Then, in the constant temperature and humidity chamber, the thermal gradient tester (BIG HEART) manufactured by Imoto Manufacturing was adjusted to 10°C at one end and 30°C at the other end. After confirming that the thermal gradient on the tester reached 1°C per 4 cm, the water dispersion was applied on the tester using a 0.2 mm applicator and dried for 12 hours. The highest temperature at which cracks with a diameter of more than 1 mm were generated on the coating was taken as the minimum film forming temperature (MFT). MFT was measured 10 times for one sample, and the average value was used.

[0293] The aqueous dispersions obtained in the examples and comparative examples were stored at 23°C, and the MFT was measured every one month. When the MFT of the 0th month is T0 and the MFT of the nth month is Tn, the change in MFT ΔMFT is calculated from Tn-T0. At the time n when ΔMFT≧4°C is satisfied, the film-forming property is considered to be impaired, and the time when ΔMFT≧4°C is satisfied for the first time is taken as the limit of the film-forming property after long-term storage (film-forming life).

[0294] For example, when the MFT is 12° C. in the 0th month, 13° C. in the 1st month, and 16° C. in the 2nd month, the film-forming life of the aqueous dispersion is 2 months.

[0295] <Monomer Composition>

[0296] The monomer compositions of the vinyl halide copolymers of Examples and Comparative Examples were evaluated by dissolving a sample collected by the following method in tetrahydrofuran-d8 and performing NMR measurement.

[0297] 10 ml of the aqueous dispersion was freeze-dried and 0.5 g of the freeze-dried product was collected. The collected freeze-dried product was dissolved in 10 ml of tetrahydrofuran with a purity of 99.9 wt% or more, and 40 ml of methanol was added dropwise to the resulting solution. The generated precipitate was filtered and the insoluble components remaining after filtration were collected. The collected insoluble components were used as the measurement sample.

[0298] The measurement conditions of NMR are shown in the following table.

[0299] Device: JEOL RESONANCE ECS400 (1H)

[0300] Bruker Biospin Avance600(13C)

[0301] Observed nuclei: 1H (399.78MHz), 13C (150.91MHz)

[0302] Pulse program: single pulse (1H), zgig30 (13C)

[0303] Integration times: 256 times (1H), 10000 times (13C)

[0304] Lock solvent: THF-d8

[0305] Chemical shift standard: THF (1H: 180ppm, 13C: 67.38ppm)

[0306] The composition of the copolymer was identified by integrating the peaks using the obtained NMR spectrum. The types of monomers contained were known from the monomers charged.

[0307] As an example, in the case of a polymer containing structural units derived from vinylidene chloride, methacrylonitrile, methyl methacrylate, and acrylic acid, in the 13C-NMR spectrum, the content of structural units derived from vinylidene chloride is calculated by integrating 80 to 90 ppm, the content of structural units derived from methacrylonitrile is calculated by integrating 110 to 130 ppm, the content of structural units derived from methyl methacrylate is calculated by integrating 170 to 180 ppm, and the content of structural units derived from acrylic acid is calculated by integrating 180 to 200 ppm, and the constituent ratio of each monomer in the whole is calculated.

[0308] In the case of a copolymer containing a structural unit derived from methyl acrylate instead of methyl methacrylate, the calculation is performed by replacing methyl methacrylate in the above calculation method with methyl acrylate.

[0309] In the case of a copolymer containing a structural unit derived from acrylonitrile instead of methacrylonitrile, the calculation is performed by replacing methacrylonitrile in the above calculation method with acrylonitrile.

[0310] It is understood that the polymers obtained in Examples and Comparative Examples have the same monomer composition as the feed composition in the above measurement results.

[0311]

[0312] The experimental results of Examples and Comparative Examples are shown.

[0313] The results in Table 1 demonstrate that the aqueous dispersion of the vinyl halide copolymer of the present invention has the following effects: the film after coating maintains high water vapor barrier properties and has excellent film-forming properties after long-term storage.

[0314] Industrial Applicability

[0315] The aqueous dispersion of the halogenated vinyl copolymer of the present invention has excellent water vapor barrier properties and film-forming properties after long-term storage after coating, and can be suitably used as a coating for various materials such as food and drug packaging films, paper, and general household products.

Claims

1. An aqueous dispersion of a halogenated vinyl copolymer, characterized in that: The aqueous dispersion comprises a vinyl halide copolymer, wherein the vinyl halide copolymer comprises a structural unit derived from a vinyl halide monomer and a structural unit derived from a comonomer having a reactivity ratio r1 with respect to vinylidene chloride of less than 0.7, With respect to 100 parts by mass of the total of the structural unit derived from the vinyl halide monomer, the structural unit derived from the comonomer having the reactivity ratio r1 of less than 0.7, and the structural unit derived from the comonomer having the reactivity ratio r1 of 0.7 or more, the mass ratio of the structural unit derived from the comonomer having the reactivity ratio r1 of less than 0.7 is 1 part by mass or more, With respect to 100 parts by mass of the total of the structural unit derived from the vinyl halide monomer, the structural unit derived from the comonomer having the reactivity ratio r1 of less than 0.7, and the structural unit derived from the comonomer having the reactivity ratio r1 of 0.7 or more, the mass ratio of the structural unit derived from the comonomer having the reactivity ratio r1 of 0.7 or more is 3 parts by mass or less, The mass ratio of the structural unit derived from the vinyl halide monomer is 87 parts by mass or more relative to 100 parts by mass of the total of the structural unit derived from the vinyl halide monomer, the structural unit derived from the comonomer having the reactivity ratio r1 of less than 0.7, and the structural unit derived from the comonomer having the reactivity ratio r1 of 0.7 or more, The mass ratio of the structural unit derived from methacrylonitrile is 1 part by mass or more relative to 100 parts by mass of the total of the structural unit derived from the vinyl halide monomer, the structural unit derived from the comonomer having the reactivity ratio r1 of less than 0.7, and the structural unit derived from the comonomer having the reactivity ratio r1 of 0.7 or more, The comonomer having a reactivity ratio r1 of less than 0.7 is methacrylonitrile and at least one selected from the group consisting of methyl methacrylate, ethyl acrylate, acrylic acid, acrylonitrile and methacrylic acid, which are optionally included. The comonomer having a reactivity ratio r1 of 0.7 or more is at least one selected from the group consisting of vinyl chloride, methyl acrylate and butyl acrylate, When the area of ​​the melting peak having a melting peak temperature of 170° C. or higher is defined as S1 and the area of ​​the melting peak having a melting peak temperature of less than 170° C. is defined as S2, S1 / (S1+S2) is from 0 to 0.33, The halogenated vinyl monomer is vinylidene chloride, In the preparation of the aqueous dispersion of the halogenated vinyl copolymer, a polymerization activator is added.

2. The aqueous dispersion of the halogenated vinyl copolymer according to claim 1, wherein Relative to 100 parts by mass of the total of the structural units derived from the vinyl halide monomer, the structural units derived from the comonomer having the reactivity ratio r1 of less than 0.7, and the structural units derived from the comonomer having the reactivity ratio r1 of 0.7 or more, the mass ratio of the structural units derived from the comonomer having the reactivity ratio r1 of less than 0.7 is 14 parts by mass or less.

3. The aqueous dispersion of the halogenated vinyl copolymer according to claim 2, wherein In 100% by mass of the vinyl halide copolymer, the total mass ratio of the structural units derived from the vinyl halide monomer and the structural units derived from the comonomer having a reactivity ratio r1 of less than 0.7 is 90% by mass or more.

4. The aqueous dispersion of the halogenated vinyl copolymer according to claim 1, wherein The mass ratio of the structural unit derived from methacrylonitrile is 1.5 parts by mass or more relative to 100 parts by mass of the total of the structural unit derived from the vinyl halide monomer, the structural unit derived from the comonomer having the reactivity ratio r1 of less than 0.7, and the structural unit derived from the comonomer having the reactivity ratio r1 of 0.7 or more.

5. The aqueous dispersion of the halogenated vinyl copolymer according to claim 4, wherein The mass ratio of the structural unit derived from methacrylonitrile is 3 parts by mass or more relative to 100 parts by mass of the total of the structural unit derived from the vinyl halide monomer, the structural unit derived from the comonomer having the reactivity ratio r1 of less than 0.7, and the structural unit derived from the comonomer having the reactivity ratio r1 of 0.7 or more.

6. The aqueous dispersion of the halogenated vinyl copolymer according to claim 5, wherein The mass ratio of the structural unit derived from methacrylonitrile is 5 parts by mass or more relative to 100 parts by mass of the total of the structural unit derived from the vinyl halide monomer, the structural unit derived from the comonomer having the reactivity ratio r1 of less than 0.7, and the structural unit derived from the comonomer having the reactivity ratio r1 of 0.7 or more.

7. The aqueous dispersion of the halogenated vinyl copolymer according to any one of claims 1 to 6, wherein The mass ratio of the structural unit derived from the comonomer having a reactivity ratio r1 of less than 0.7 is 5 parts by mass or more and 20 parts by mass or less.

8. The aqueous dispersion of the halogenated vinyl copolymer according to any one of claims 1 to 6, wherein The S1 / (S1+S2) is greater than or equal to 0 and less than or equal to 0.

31.

9. The aqueous dispersion of the halogenated vinyl copolymer according to any one of claims 1 to 6, wherein The S1 / (S1+S2) is greater than or equal to 0 and less than or equal to 0.

26.

10. The aqueous dispersion of the halogenated vinyl copolymer according to any one of claims 1 to 6, wherein The crystal nucleating agent is contained in an amount of 20 parts by mass or less based on 100 parts by mass of the halogenated vinyl copolymer.

11. The aqueous dispersion of the halogenated vinyl copolymer according to claim 7, wherein The crystal nucleating agent is contained in an amount of 20 parts by mass or less based on 100 parts by mass of the halogenated vinyl copolymer.

12. The aqueous dispersion of the halogenated vinyl copolymer according to claim 8, wherein The crystal nucleating agent is contained in an amount of 20 parts by mass or less based on 100 parts by mass of the halogenated vinyl copolymer.

13. The aqueous dispersion of the halogenated vinyl copolymer according to claim 9, wherein The crystal nucleating agent is contained in an amount of 20 parts by mass or less based on 100 parts by mass of the halogenated vinyl copolymer.

14. The aqueous dispersion of the halogenated vinyl copolymer according to any one of claims 1 to 6, wherein The comonomer having a reactivity ratio r1 less than 0.7 is methacrylonitrile.

15. A film, characterized in that It has a layer coated with the aqueous dispersion of the ethylene halide copolymer according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Production of copolymer-coated material

    JP1985192768A

  • Water-based polymer dispersion

    JP1993202107A

  • Process for preparing aqueous dispersions of polymers, resulting aqueous dispersions and uses thereof

    JP2001526315A

  • Vinylidene chloride copolymer latex and film for blister pack

    WO2013125699A1

  • Vinylidene chloride coplymers

    GB1519548A